Appropriateness rating for the application of optimal medical therapy and multidisciplinary care among heart failure patients. (17th November 2020) - Shoji, Satoshi; Kohsaka, Shun; Shiraishi, Yasuyuki; Oishi, Shogo; Kato, Mahoto; Shiota, Shigehito; Takada, Yasuko; Mizuno, Atsushi; Yumino, Dai; Yokoyama, Hiroyuki; Watanabe, Noboru; Isobe, Mitsuaki
Abstract: Aims: Clinical guidelines for improving the patients' quality of care vary in clinical practice, particularly in super‐aging societies, like in Japan. We aimed to develop a set of appropriate‐use criteria (AUC) for contemporary heart failure (HF) management to assist physicians in decision making. Methods and results: With the use of the RAND methodology, a multidisciplinary writing group developed patient‐based clinical scenarios in 10 selected key topics, stratified mainly by HF stage, age, and renal function. Nine nationally recognized expert panellists independently rated the clinical scenario appropriateness twice on a scale of 1–9, as 'appropriate' (7–9), 'may be appropriate' (4–6), or 'rarely appropriate' (1–3). Decisions were based on clinical evidence and professional opinions in the context of available resource use and costs. An interactive round‐table discussion was held between the first and second ratings; the median score of the nine experts was then assigned to an appropriate‐use category. Most clinical scenarios without strong evidence were evaluated as 'may be appropriate'. Frailty assessments in elderly patients (age ≥ 75 years), regardless of the HF stage, and advanced care planning in patients with stage C/D HF, regardless of age, were considered 'appropriate'. For HF with reduced ejection fraction, beta‐blocker administration in elderly patients (age ≥ 75 years) with heart rate < 50 b.p.m. and mineral corticosteroid receptor antagonist use in elderly patients (age ≥ 75 years) with an estimated glomerular filtration rate < 30 mL/min/1.73 m 2 were considered 'rarely appropriate'. Conclusions: The HF management AUC provide a practical guide for physicians regarding scenarios commonly encountered in daily practice.